Would you rather treat? A rare case of Mycobacterium scrofulaceum - Junaid Zafar Sheikh; Nonhlanhla Lunjani; Hira Gul; Louay Kila; Brian Casserly (European Journal of Case Reports in Internal Medicine)
Mycobacterium scrofulaceum is a rare cause of non-tuberculous mycobacterial infection in adults, primarily affecting the immunocompromised. Pulmonary involvement has been seen in individuals with pre-existing lung pathology. We report a case of a 63-year-old female who presented with abdominal pain, cough and sputum samples yielding M. scrofulaceum, with a normal clinical examination. Initial investigations were unremarkable, prompting abdomen and pelvis computed tomography (CT), revealing minimal pericardial and ascitic fluid. Thoracic CT exhibited calcified tree-in-bud nodules and a trivial left pleural effusion. Given subdued symptoms and limited disease, discerning colonisation versus clinically relevant infection was uncertain. Due to lack of empirical data for guidance, treatment approaches at this juncture remain unclear. The patient was monitored closely for a period of one year with a plan to treat should there be evidence of active disease.